Tahap pengetahuan, kefahaman, sikap dan amalan terhadap keselamatan di organisasi pendidikan - Azad, Othman (2013)
This study aims to identify level of understanding, knowledge, practice, and attitude towards safety measures in workshops during integrated living skill practical session. Additionally, this study discerns the relationships among each construct that is related to the safety measures. The teachers’ perception towards safety measures while teaching integrated living skills in workshop has also been elucidated. Quantitative as well as qualitative methods have been employed with survey form are utilized in obtaining meaningful data. Apart from survey, an in-depth interview with teachers on safety measures has also been used. The researcher has recruited 300 form three students as respondents from selected schools in Pahang state and 10 specialist teachers of integrated living skills have been interviewed. The quantitative finding shows that overall mean score for level of knowledge is 3.00; min value for attitude is 2.54; min value for level of implementation is 2.38; and min value for level of understanding is 2.29. This indicates that level of safety among students in workshop is low. Whereas correlation analysis found that value r = 0.449 for level of understanding and implementation. The value r = 0.324 stated for level of knowledge and attitude. The findings identified some weak positive correlations among constructs tested. Furthermore, based on in-depth interview with specialist teachers found contrary perception compared to pupils’ point of view. Some conclusions have been drawn based on the research questions that will be referred for future studies.